Pengaruh Risiko Bisnis, Keputusan Investasi, dan Kepemilikan Manajerial terhadap Kinerja Keuangan Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Afifah, Nabila; Martha, Lidya (ARZUSIN, 2026)
Although studies on the factors influencing corporate financial performance have been widely conducted, discussions that specifically examine the role of business risk, investment decisions, and managerial ownership in manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period still need to be strengthened. This study aims to analyze the effect of business risk, investment decisions, and managerial ownership on the financial performance of manufacturing companies. This study used a quantitative approach with an associative design. The research sample consisted of 19 companies selected through purposive sampling, resulting in 53 observational data. Data were collected through documentation of manufacturing companies’ financial reports published on the official website of the Indonesia Stock Exchange and analyzed using panel data regression with the assistance of EViews. The results showed that business risk had a negative and insignificant effect on financial performance, whereas investment decisions and managerial ownership had a positive and significant effect on financial performance. These findings strengthen the relevance of Signaling Theory in explaining the relationship between managerial decisions, ownership structure, and financial performance. The conclusion of this study emphasizes the importance of investment policies and managerial ownership in supporting the improvement of manufacturing companies’ financial performance. The implications of this study include theoretical contributions to the development of corporate finance literature and practical implications for management in formulating more effective investment strategies and ownership structure management.